Wedding night - Kinsella, Sophie (Black Swan, 2013)
It's all gone wrong with the man Lottie thought was Mr Right. Then out of the blue she gets a call from her first love. She decides it must be Fate, and rushes off to marry him and rekindle their sizzling Greek island romance. Lottie's older sister can't believe she's doing something so crazy. No more Ms Nice Sister, she's stopping this marriage. Right away! and she'll go to any lengths to do so...